2016
DOI: 10.5194/gmd-9-1455-2016
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic, Lagrangian model of sinking biogenic aggregates in the ocean (SLAMS 1.0): model formulation, validation and sensitivity

Abstract: Abstract. We present a new mechanistic model, stochastic, Lagrangian aggregate model of sinking particles (SLAMS) for the biological pump in the ocean, which tracks the evolution of individual particles as they aggregate, disaggregate, sink, and are altered by chemical and biological processes. SLAMS considers the impacts of ballasting by mineral phases, binding of aggregates by transparent exopolymer particles (TEP), zooplankton grazing and the fractal geometry (porosity) of the aggregates. Parameterizations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 119 publications
(124 reference statements)
0
31
0
Order By: Relevance
“…In particular, this distribution may depend on the structure of the ecosystem in the euphotic zone. Biochemical analysis of the surface particulate organic matter has shown that its composition varies both in time and space as a result of differences in the phytoplankton and zooplankton species and interactions (Tegelaar et al, 1989;Kiriakoulakis et al, 2001;Lee et al, 2004;Mayzaud et al, 2014). Thus, the lability distribution of POM is unlikely to be constant both in time and space.…”
Section: Spatial Variations Of Remineralisation Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, this distribution may depend on the structure of the ecosystem in the euphotic zone. Biochemical analysis of the surface particulate organic matter has shown that its composition varies both in time and space as a result of differences in the phytoplankton and zooplankton species and interactions (Tegelaar et al, 1989;Kiriakoulakis et al, 2001;Lee et al, 2004;Mayzaud et al, 2014). Thus, the lability distribution of POM is unlikely to be constant both in time and space.…”
Section: Spatial Variations Of Remineralisation Efficiencymentioning
confidence: 99%
“…With the notable exception of Sempéré et al (2000), the inhomogeneous reactivity of POC has not been explicitly taken into account in marine biogeochemical modelling studies; the vast majority of the models use a single uniform decay rate for the whole particulate organic pool. Very recently, Jokulsdottir and Archer (2016) have designed a very detailed Lagrangian model of POC which explicitly assumes that aggregates are composed of various compounds with different labilities, in a manner similar to our approach. Unfortunately, they have not explored in their study the impacts this varying lability has on the POC distribution and on the POC fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies [8][9][10][11] have formulated prognostic models for the sinking particle flux. Kriest and Oschiles 12 examined what sinking characteristics contribute to a 'Martin curve' like flux profile and showed that a constant sinking velocity does not produce the characteristic attenuation in the profile.…”
mentioning
confidence: 99%
“…This has potentially useful implications for modelling the remineralisation of particulate organic matter fluxes. Models resolving the various processes that affect remineralisation rates and sinking velocities have recently been developed (Jokulsdottir and Archer, 2016;Cram et al, 2018) however, the requirements to model processes such as particle aggregation can be computationally expensive, limiting their application to 1-D models (Jokulsdottir and Archer, 2016;Cram et al, 2018) or to offline models (DeVries et al, 2014). A globally uniform change in b informed by these models could then used to calculate the impact on atmospheric CO 2 if the change in b is greater than 0.2.…”
Section: Discussionmentioning
confidence: 99%